Dealers' insurance, market structure, and liquidity - Francesca Carapella; Cyril Monnet (University of Bern, Department of Economics, 2018)
We develop a parsimonious model to study the equilibrium structure of over-the-counter securities markets. We show that regulations aimed at reducing counterparty risk and improving liquidity can be ineffcient. Such regulations have a direct positive effect on entry in those markets, thus fostering competition and lowering spreads. Greater competition, however, has an indirect negative effect on market making profitability, this effect being stronger on more effcient intermediaries. Thus, general equilibrium effects result in reduced incentives of all intermediaries to invest in effcient technologies and can cause a social welfare loss. The equilibrium outcome is consistent with some empirical findings on the effects of post-crisis regulations and with the observed resistance by some market participants to those regulations.
Keywords: G11; G23; G28; 330; Liquidity; dealers; insurance; central counterparties